Village Based Participatory Breeding in the Mountain Slopes of Yemen - Ceccarelli, Salvatore (International Center for Agricultural Research in the Dry Areas, 2002)
In the three villages selected in the project area in the Northern Highlands and described in the 2000 reports, the farmers tested the barley and the lentil lines they selected during 2000.